Research on potential biomarkers in hereditary hemorrhagic telangiectasia - Botella, Luisa-María; Albiñana, Virginia; Ojeda-Fernandez, Luisa; Recio-Poveda, Lucia; Bernabéu, Carmelo (Frontiers in Genetics, 2015)
Hereditary Hemorrhagic Telangiectasia (HHT) is a genetically heterogeneous disorder, involving mutations in two predominant genes known as Endoglin (ENG; HHT1) and Activin receptor like kinase 1 (ACVRL1/ALK1; HHT2), as well as in some less frequent genes, such as MADH4/SMAD4 (JP-HHT) or BMP9/GDF2 (HHT5). The diagnosis of HHT patients currently remains at the clinical level, according to the “Curaçao criteria”, whereas the molecular diagnosis is used to confirm or rule out suspected HHT cases, especially when a well characterized index case is present in the family or in an isolated population. Unfortunately, many suspected patients do not present a clear HHT diagnosis or do not show pathogenic mutations in HHT genes, prompting the need to investigate additional biomarkers of the disease. Here, several HHT biomarkers and novel methodological approaches developed during the last years will be reviewed. On one hand, products detected in plasma or serum samples: soluble proteins (VEGF, TGF-β1, soluble endoglin, angiopoietin-2) and microRNA variants (miR-27a, miR-205, miR-210). On the other hand, differential HHT gene expression fingerprinting, Next Generation Sequencing (NGS) of a panel of genes involved in HHT, and infrared spectroscopy combined with Artificial Neural Network (ANN) patterns will also be reviewed. All these biomarkers might help to improve and refine HHT diagnosis by distinguishing from the non-HHT population.